Analysis of Oxidized Pt Species on a Connected Pt–Fe Catalyst with Enhanced Oxygen Reduction Activity Probed by Electrochemical XPS - Hidenori Kuroki; Masashi Matsumoto; Takanori Tamaki; Hideto Imai; Takeo Yamaguchi (Journal of Chemical Engineering of Japan, 2023)
An oxygen reduction reaction (ORR) activity of platinum (Pt)-based catalysts for polymer electrolyte fuel cells correlates with the adsorption characteristics of oxygen species during ORR on Pt surfaces and Pt oxidation (poisoning) by water. This study analyzed the oxidized Pt species (Pt–Oad/OHad, PtO, and PtO2) that were generated by the reaction with O2 and H2O on the Pt surfaces of a highly active carbon-free connected platinum–iron (Pt–Fe) catalyst and a conventional Pt/C catalyst. The analysis was performed by electrochemical X-ray photoelectron spectroscopy (XPS) measurements using Pt 4f XPS spectra of the catalysts after immersion in a perchloric acid (HClO4) electrolyte solution with specific applied potentials. The results showed that Pt surfaces of the connected Pt–Fe catalyst exhibited less oxidation (lower coverage of Oad/OHad, PtO, and PtO2) by water and more O-species adsorption (higher coverage of Oad/OHad) under the ORR, indicating that the characteristic structure of the connected Pt–Fe catalyst unlike a Pt/C catalyst is beneficial for enhancement of the ORR activity in terms of O-species adsorption and oxide formation on a Pt surface.